2019
DOI: 10.1111/bju.14638
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and the Rho‐kinase inhibitor Y‐27632 prevent myofibroblast transformation in Peyronie's disease‐derived fibroblasts via inhibition of YAP/TAZ nuclear translocation

Abstract: ObjectivesTo uncover the anti-myofibroblast (MFB) properties of Rhokinase inhibitor (compound Y-27632) and simvastatin in an in vitro model of Peyronie's disease (PD), a sexually debilitating disease caused by an irreversible fibrotic plaque in the penile tunica albuginea (TA). ConclusionTransformation of FBs into the contractile and extracellular matrix-producing MFBs occurs after TGF-b1 stimulation. In our experiments, Rho-kinase inhibition and simvastatin treatment were shown to prevent this in TGF-b1-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Some studies have demonstrated the inhibitory effects of simvastatin and Y-27632 on TGF-b-induced myofibroblast differentiation from fibroblasts derived from different disease specimens, such as nasal polyps (24), keloids (20), and penile tunica albuginea from Peyronie's disease (21). To the best of our knowledge, this is the first study to investigate the antifibrotic effects of simvastatin and Y-27632 in GO-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Some studies have demonstrated the inhibitory effects of simvastatin and Y-27632 on TGF-b-induced myofibroblast differentiation from fibroblasts derived from different disease specimens, such as nasal polyps (24), keloids (20), and penile tunica albuginea from Peyronie's disease (21). To the best of our knowledge, this is the first study to investigate the antifibrotic effects of simvastatin and Y-27632 in GO-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 86%
“…Statins inhibit the synthesis of intermediates of cholesterol biosynthesis such as farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP), which are essential for the post-translational modification of the Rho family proteins (8). Therefore, statins have a potential therapeutic role in fibrotic diseases owing to their inhibitory effects on RhoA/ROCK signaling (20,21). Simvastatin, a type of statin, can suppress TGF-b-induced myofibroblast transformation of fibroblasts through RhoA/ROCK inhibition (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is reported that TGFβ1 is a possible driver of Rho-associated coiled-coil protein kinase (ROCK) ( Milenkovic et al, 2019d ). Activation and up-regulation of ROCK have been examined in the corpora cavernosa following neuropraxia ( Sezen et al, 2014 ).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Meanwhile, Rho/RhoA signaling works partly through nuclear translocation of YAP/TAZ ( Knipe et al, 2015 ). Y-27632, a ROCK inhibitor, coupled with simvastatin has been shown to suppress the TGF-β1-induced myofibroblast transformation by prevention of YAP/TAZ nuclear translocation ( Milenkovic et al, 2019d ). In this respect, the inhibition of YAP/TAZ nuclear translocation might have anti-fibrotic effects, providing a novel target for PD.…”
Section: Pharmacotherapy For Pdmentioning
confidence: 99%